You Ci Ke - Fong, Ronald Ren Kai (2015)
You Ci Ke有刺客 is a short animated film packed with humour and action. On top of the visual humour, the film seeks to convey in a positive and light-hearted manner that the best intentions of the everyday man, much like protagonist Nucai, do not always pay off. In order to not let the film become too heavy hearted, acting choices, color palette and design direction of the film were carefully crafted, ensuring that the film remains accessible and fun to watch. This report documents the process of making this final year project (FYP) thesis film from its early stages to the final renders, highlighting artistic and technical decisions made along the way. It introduces the challenges faced while creating the film, most notably in designing a stylised art direction of the film, as well as the techniques that were developed and implemented to overcome these challenges.